Optimizing the anaerobic co-digestion of brown water and food waste for clean energy recovery, by phase separation and microaerotion : laboratory reactor performance and microbial community profiling - Lim, Jun Wei (2015)
The objective of this research was to determine the reactor configuration and operating parameters suitable for efficient energy recovery from the anaerobic co-digestion of brown water (BW) and food waste (FW). This was achieved through biochemical methane potential (BMP) tests, 5 L and 30 L reactor performance studies and microbial community profiling for the anaerobic co-digestion of BW and FW. Preliminary BMP tests demonstrated the advantages of co-digestion, in terms of higher methane yield and organic matter removal efficiencies, as compared to the anaerobic digestion of the substrates individually. Long-term reactor performance studies coupled with microbial community profiling showed that two-phase CSTR systems will likely lead to more stable treatment of BW and FW mixtures. The effect of microaeration on the co-digestion system was also investigated by carrying out BMP tests, fed-batch reactor studies and microbial analysis. Microaeration was shown to enhance methane yield through higher COD solubilization and VFA accumulation. Analysis of the microbial community structure also revealed how microaeration improved the fermentation process during the anaerobic co-digestion of BW and FW. The positive findings in this research show the great potential of applying anaerobic co-digestion of BW and FW for energy production and waste management in the proposed decentralized and source-separation-based sanitation concept.